Magnetic field induced ferromagnetim in EuPd2Sn4 novel compound - Curlík, Ivan; Zapotoková, Mariana; Gastaldo, Federica; Reiffers, Marián; Sereni, Julian Gustavo Renzo; Giovanini, Mauro (Wiley VCH Verlag, 2021)
Fil: Curlík, Ivan. University of Preshov; Eslovaquia